A new multidimensional design space identification method for a quality-oriented drug development process. (3rd July 2016) - Choi, Gyuhyo; Le, Tuan-Ho; Shin, Sangmun
Abstract : Food and Drug Administration and the European Medicines Agency have tightened regulations pertaining to drug manufacturing and research based on the concept of Quality by Design (QbD) in order to improve drug quality and safety. Although many QbD methods have been reported in the pharmaceutical research community, there is room for improvement associated with design space identification. The primary motivation of this paper is to propose an alternative identification method for generating a safe, multidimensional design space for quality-oriented drug development. First of all, the functional relationships between input factors and their associated output responses are exploited and estimated by using response surface methodology (RSM). Second, the normal acceptable ranges can also be obtained while customising statistical confidence and prediction intervals for RSM. Following this, a safe multidimensional design space is generated on an overlay contour plot including the importance of input factors. Finally, a case study for a drug development process is performed for verification purposes. From the proposed method, significant improvement in drug quality through factors such as variability reduction, statistical reliability, and the reproducibility of quality characteristics can be achieved.